2020
DOI: 10.1212/nxi.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and stress markers predicting pneumonia, outcome, and etiology in patients with stroke

Abstract: ObjectivePrognosis of stroke is negatively affected by complications, in particular stroke-associated pneumonia (SAP). We hypothesized that inflammatory and stress biomarkers predict SAP during hospitalization and outcome 3 months after stroke.MethodsWe pooled the clinical data of 2 acute stroke studies with identical assessment: the STRoke Adverse outcome is associated WIth NoSoKomial Infections (STRAWINSKI) and PREDICT studies. Measurement of biomarkers (ultrasensitive procalcitonin [PCTus]; midregional pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Recently, PCT and copeptin were studied as SAP predictors along with other biomarkers by pooling data from two clinical trials (PREDICT [ 62 ] and STRAWINSKI [ 63 ]). Of all the studied biomarkers, the results showed that only PCT and copeptin were independent predictors of SAP when adjusting for clinical variables such as dysphagia, chronic obstructive pulmonary disease (COPD), hypercholesterolemia, and the National Institute of Health Stroke Scale (NIHSS) at admission [ 64 ]. In contrast, at earlier time points, Hu et al [ 65 ] did not find PCT to be useful for the prediction of SAP, only when the clinical suspicion of SAP is already high.…”
Section: Clinical Implications (1): the Use Of Cellular And Molecular Changes As Biomarkers For The Prediction Of Stroke-associated Infecmentioning
confidence: 99%
“…Recently, PCT and copeptin were studied as SAP predictors along with other biomarkers by pooling data from two clinical trials (PREDICT [ 62 ] and STRAWINSKI [ 63 ]). Of all the studied biomarkers, the results showed that only PCT and copeptin were independent predictors of SAP when adjusting for clinical variables such as dysphagia, chronic obstructive pulmonary disease (COPD), hypercholesterolemia, and the National Institute of Health Stroke Scale (NIHSS) at admission [ 64 ]. In contrast, at earlier time points, Hu et al [ 65 ] did not find PCT to be useful for the prediction of SAP, only when the clinical suspicion of SAP is already high.…”
Section: Clinical Implications (1): the Use Of Cellular And Molecular Changes As Biomarkers For The Prediction Of Stroke-associated Infecmentioning
confidence: 99%
“…Hence, the diagnosis of an ischemic stroke is currently linked to the detection of a persistent and not only transient neuronal damage either by cerebral imaging in terms of an ischemic lesion or by persisting neurological symptoms for more than 24 h ( 3 ). Besides the differentiation between ischemic and hemorrhagic stroke within the (hyper)acute phase of stroke ( 5 , 6 ), serum biomarkers might also be helpful in predicting complications of stroke like pneumonia ( 11 , 13 ), in functional prognostication ( 12 , 14 , 15 ), as well as in the allocation of diagnostic and rehabilitative resources. However, so far, no single biomarker or panel of biomarkers succeeded translation from bench to bedside, i.e., to facilitate diagnosis, treatment, or prognostication ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, it has been recently included in a validated biomarker-based clinical score with age, NIHSS and thrombolysis, "the CoRisk score", for the prediction of 90-day death and disability after ischemic stroke (AUC 0.819) [114]. Data from a recent pooled analysis indicate copeptin is an independent predictor of stroke-associated pneumonia, although of only slightly additive value as compared with clinical parameters or commonly applied prediction scores [115,116], and that its plasma levels are higher in cardioembolic stroke than other etiologies [115]. Furthermore, assessing copeptin levels in the emergency setting could be helpful in guiding the safe discharge of patients with transient ischemic attack (TIA) and their subsequent management as outpatients [117]: in a prospective observational study on 237 consecutive patients referring to the emergency department for TIA, copeptin emerged as an independent predictor for stroke recurrence within 7 days (negative predictive value 97.4% at a cut-off value of 13.8 pmol/L, HR 3.9, 95% CI 1.01-14.4, p = 0.039), particularly when combined with demonstrated large artery atherosclerosis (HR 7.8, 95% CI 2.5-24.7, p = 0.002; AUC 0.83).…”
Section: Neurological Illnessesmentioning
confidence: 99%